Integration of Mobile-Assisted Language Learning (MALL) Using Quizlet to Enhance EFL Students' Vocabulary Mastery - Hisasmaria (PT MEDIA JURNAL DAN PENDIDIKAN, 2025)
Vocabulary mastery is a foundational element in English as a Foreign Language (EFL) acquisition, yet traditional instructional methods often fail to maintain student engagement and retention. This study aims to investigate the effectiveness of integrating Quizlet, a Mobile-Assisted Language Learning (MALL) application, to significantly improve the vocabulary mastery of first-semester students at Universitas Pohuwato. Employing a quantitative pre-experimental research design (one-group pre-test and post-test), the study involved a sample of 23 students selected through a total sampling technique. Primary data were collected utilizing a validated 25-item multiple-choice vocabulary test administered before and after a four-meeting instructional treatment. The collected data were analyzed using descriptive statistics and a paired sample t-test via SPSS. The findings revealed a substantial increase in students' learning outcomes; the pre-test mean score of 62.13 rose significantly to a post-test mean of 81.74. Inferential analysis yielded a significance value of 0.000 (p < 0.05) with a t-value of -9.87, unequivocally rejecting the null hypothesis. The integration of Quizlet’s interactive flashcards and gamified repetition fostered an engaging, independent learning environment that successfully bridged the vocabulary deficit. In conclusion, Quizlet is a highly effective pedagogical tool for vocabulary acquisition, and it is strongly recommended that EFL educators incorporate such digital applications into their teaching strategies.